Brunet Saunier architecture : monospace and simplexty - Blin, Pascale (De Gruyter, 2012)
Founded in 1981 in Paris, Brunet Saunier Architecture is a French leader in the design of hospitals and large-scale public buildings. This publication is much more than a monograph. It is also a professional reference work, as hospital buildings make up a large portion of the showcased projects. Over the last ten years the architectural office has been developing a successful concept known as "Monospace". The book discusses and analyzes this concept in detail, presenting trueto- scale floor plans, cross-sections, architectural views, and other information. The Monospace concept - which is base.